PENGARUH KEGIATAN BERMAIN MELEMPAR BOLA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK ASSISI MEDAN - Ernis Hiasinta Ginting; Damaiwaty Ray (JURNAL TEMATIK, 2018)
This study aims to determine the effect of playing throwing balls on the gross motoric development of children aged 4-5 years. This study uses a quantitative approach with an experimental method with a Quasi Exprerimental Design design with the form Nonequivalent Control Group Design. Determination of class samples is done randomly. The results of the descriptive analysis showed that the game of throwing the ball was better than the control class, the highest score was 18, while the control class obtained the highest score of 14, the average for the experimental class was 14.54 and for the control class 10.68. The number of children who scored above the average in the experimental class were 11 children (50%) while in the control class the children who got the above scores had an average of 8 children (36.36%), whereas the number of children in the control class who scored below the average more (54.54%) than in the experimental class (45.5%). Based on the results of these data states that the data is normally distributed and has the same or homogeneous variance fulfilled for both groups of data. Hypothesis test results are known t_ (count) = 6.012> t_table = 1.685. This shows that there is a significant influence between the activity of playing throwing the ball against the gross motoric development of children aged 4-5 years.